Pregnancy complications in HIV‐positive women: 11‐year data from the Frankfurt HIV Cohort. Issue 9 (6th March 2014) - Reitter, A; Stücker, AU; Linde, R; Königs, C; Knecht, G; Herrmann, E; Schlößer, R; Louwen, F; Haberl, A
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess pregnancy complications in HIV‐positive women and changes in the rates of such complications over 11 years in the Frankfurt HIV Cohort. Methods There were 330 pregnancies in HIV‐positive women between 1 January 2002 and 31 December 2012. The rate of pregnancy‐related complications, such as gestational diabetes mellitus (GDM), pre‐eclampsia and preterm delivery, the mode of delivery and obstetric history were analysed. Maternal and neonatal morbidity/mortality as well as HIV mother‐to‐child transmission (MTCT) were evaluated. Results In our cohort, GDM was diagnosed in 38 of 330 women (11.4%). Five women (1.5%) developed pre‐eclamspia or hypertension. In 16 women (4.8%), premature rupture of membranes (PROM) occurred and 46 women (13.7%) were admitted with preterm contractions. The preterm delivery rate was 36.5% (n = 122), and 26.9% of deliveries (n = 90) were between 34+0 and 36+6 weeks of gestation. Over the observation period, the percentage of women with undetectable HIV viral load (VL) increased significantly (P < 0.001), from 26.1% to 75%, leading to obstetric changes, including an increase in the rate of vaginal deliveries (P < 0.001), from no vaginal births to 50%. The preterm delivery rate decreased significantly (P < 0.001), from 79.2% to 8.3%. There were no significant changes in the rate of GDM, pre‐eclampsia, PROM or preterm contractions. Conclusions In the 11 years of our analysis, there was a significant reduction in the rate of preterm deliveries and an increase in the vaginal delivery rate, possibly reflecting changes in treatment policies in the same period and the availability of more effective antiretroviral therapy options. The rates of complications such as GDM, pre‐eclampsia, preterm contractions, PROM and postnatal complications were stable over the 11 years, but were still increased compared with the general population.